Infrared 3D Observations of Nearby Active Galaxies - Maiolino, R; Thatte, N; Alonso-Herrero, A; Lutz, D; Marconi, A (1999)
We present multi-wavelength imaging observations of three nearby and famous active galaxies obtained with NICMOS, ISOCAM and the MPE near-IR integral field spectrometer. The data reveal a variety of features and properties that are missed in optical studies and in traditional IR monodimensional spectroscopy.